Determinants of Road Traffic Accident Among Elderly in Malaysia: A Scoping Review - Bin Ibrahim, Muhammad Naim; Nik Husain, Nik Rosmawati; Mohd Kutubudin, Ahmed Farrasyah; Hanafi, Nur Sujaihah (IIUM Medical Journal Malaysia, 2025)
Malaysia is transitioning into an aged nation, with 15% of its population projected to be 60 years or older by 2030. This demographic shift is expected to increase the number of elderly road users, yet road conditions remain inadequate for their needs, and preventive measures for road traffic accidents (RTAs) are still underdeveloped. There is limited understanding of how physiological, cognitive, and environmental factors contribute to RTAs among the elderly in Malaysia. This scoping review aims to explore existing literature on the factors influencing RTAs in this demographic. The review follows the PRISMA-ScR reporting guidelines and includes peer-reviewed studies published in English from 2012 to 2022. A total of 15 studies were identified, and the findings are categorized into four domains: medical conditions, physical capability, driving nature, and environmental factors. Key determinants include cognitive impairment, medical illnesses, visual impairment, depression, and adverse medication effects (medical conditions); poor physical strength and flexibility, and fatigability (physical capability); long driving hours or distance, driving alone, and poor ergonomics (driving nature); and poor road condition and visibility, road complexity, reckless behaviour of other road users, and poorly maintained or old vehicles (environmental factors). These determinants are crucial in informing RTAs prevention strategies and guiding public health interventions for the elderly. However, the limited number of studies highlights the need for further research in this area to better support the safety of elderly road users.